Graduates' Perceptions of Learning Affordances in Longitudinal Integrated Clerkships: A Dual-Institution, Mixed-Methods Study. (September 2017) - Latessa, Robyn A.; Swendiman, Robert A.; Parlier, Anna Beth; Galvin, Shelley L.; Hirsh, David A.
Abstract : Purpose: The authors explored affordances that contribute to participants' successful learning in longitudinal integrated clerkships (LICs). Method: This dual-institutional, mixed-methods study included electronic surveys and semistructured interviews of LIC graduates who completed their core clinical (third) year of medical school. These LIC graduates took part in LICs at Harvard Medical School from 2004 to 2013 and the University of North Carolina School of Medicine–Asheville campus from 2009 to 2013. The survey questions asked LIC graduates to rate components of LICs that they perceived as contributing to successful learning. A research assistant interviewed a subset of study participants about their learning experiences. The authors analyzed aggregate data quantitatively and performed a qualitative content analysis on interview data. Results: The graduates reported multiple affordances that they perceive contributed to successful learning in their LIC. The most reported components included continuity and relationships with preceptors, patients, place, and peers, along with integration of and flexibility within the curriculum. Conclusions: As LIC models grow in size and number, and their structures and processes evolve, learners' perceptions of affordances may guide curriculum planning. Further research is needed to investigate to what degree and by what means these affordances support learning in LICs and other models of clinical education. Abstract : Supplemental Digital Content is available in the text.